High nonfasting triglyceride concentrations predict good outcome following acute ischaemic stroke. (2nd September 2017) - Kang, Kyusik; Lee, Jung-Ju; Park, Jong-Moo; Kwon, Ohyun; Han, Sang Won; Kim, Byung Kun
Abstract: Objectives : A higher fasting triglyceride (TG) concentration has been associated with better functional outcomes after stroke. Recent observational studies have found that nonfasting TG concentrations predict incident stroke better than fasting concentrations. The aim of the study was to investigate the relationship between fasting and nonfasting serum TG concentrations versus 3-month functional activity and mortality among patients with acute ischaemic stroke. Methods : This was a retrospective study based on prospectively collected data. Blood samples were taken from acute ischaemic stroke patients at the time of hospital presentation to measure nonfasting TG concentrations and on the following morning to measure fasting TG concentrations. Fasting and nonfasting serum TG concentrations were collapsed into their respective three categories. All participants were assessed at 3 months after stroke using the modified Rankin Scale. Results : A total of 556 ischaemic stroke patients (67 ± 13 years; 57% male) were included in this study. Bivariately, the highest fasting and nonfasting TG category had more of a likelihood of good 3-month functional activity and less of a likelihood of being dead at 3 months compared to their respective lowest TG categories. The highest fasting TG (OR 2.93, 95% CI 1.67–5.14) and nonfasting TG (OR 2.66, 95% CI 1.51–4.67) categories had more of a likelihood of good 3-month functional activity compared to their respective lowest TG categories after adjustment for possible confounders. Discussion : Higher fasting and nonfasting serum TG concentrations predicted good poststroke outcome independently of other prognostic factors.